Cyberpunk and visual culture - Murphy, Graham J. 1970-; Schmeink, Lars 1975- (Routledge, Taylor & Francis Group, 2018)
Within the expansive mediascape of the 1980s and 1990s, cyberpunk's aesthetics took firm root, relying heavily on visual motifs for its near-future splendor saturated in media technologies, both real and fictitious. As today's realities look increasingly like the futures forecast in science fiction, cyberpunk speaks to our contemporary moment and as a cultural formation dominates our 21st century techno-digital landscapes. The 15 essays gathered in this volume engage the social and cultural changes that define and address the visual language and aesthetic repertoire of cyberpunk - from cybernetic organisms to light, energy, and data flows, from video screens to cityscapes, from the vibrant energy of today's video games to the visual hues of comic book panels, and more. Cyberpunk and Visual Culture provides critical analysis, close readings, and aesthetic interpretations of exactly those visual elements that define cyberpunk today, moving beyond the limitations of merely printed text to also focus on the meaningfulness of images, forms, and compositions that are the heart and lifeblood of cyberpunk graphic novels, films, television shows, and video games.